2016
DOI: 10.1016/j.lwt.2015.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of lactic and malic organic acids on autoinducer type 2 (AI-2) quorum sensing of Escherichia coli O157:H7 and Salmonella Typhimurium

Abstract: Several organic acid based antimicrobials are reported to reduce bacterial populations but studies showing inhibition of autoinducer-2 (AI-2) activity or quorum sensing are limited. The effect of lactic and malic acids on autoinducer activity of selected strains of E. coli O157:H7 and Salmonella Typhimurium is tested in this study. The strains were screened for AI-2 like activity on spinach and cantaloupe homogenates using autoinducer sensing V. harveyi biosensor strains. The ED 14 strain of E. coli O157:H7 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…g ., acylated homoserine lactones and furanosyl borate diester) [ 9 , 10 ]. Marine bacterium Vibrio harveyi is commonly utilized as a bioluminescent reporter strain to detect the presence of autoinducer molecules at extremely low concentrations (< 1 nM) [ 11 ]. Multiple QS systems that impinge on the activity of a shared transcriptional regulator have also been reported in many bacterial species.…”
Section: Introductionmentioning
confidence: 99%
“…g ., acylated homoserine lactones and furanosyl borate diester) [ 9 , 10 ]. Marine bacterium Vibrio harveyi is commonly utilized as a bioluminescent reporter strain to detect the presence of autoinducer molecules at extremely low concentrations (< 1 nM) [ 11 ]. Multiple QS systems that impinge on the activity of a shared transcriptional regulator have also been reported in many bacterial species.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, quorum-sensing antagonists of either natural or synthetic origin (e.g., vanillin [89], malic and lactic acids [90], or numerous biosurfactants [91]) are able to interfere with the receptor-binding process. Some of these compounds are produced by thermophiles and halophiles and hence make them suitable for application in seawater cooling tower systems and seawater injection systems.…”
Section: Introductionmentioning
confidence: 99%
“…UPLC-MS/MS results in this study revealed that organic acids are one of the principal components of CFEE. None of these organic acids have been reported to have QSI activity, except malic acid which has been reported to have inhibitory effect on AI-2 QS system of E. coli O157:H7 and S. typhimurium [ 33 ]. Our results demonstrate for the first time that malic acid and succinic acid have inhibitory effects on the AI-1 QS system of C. violaceum 026.…”
Section: Resultsmentioning
confidence: 99%